Chemometric Analysis for Heavy Metal Pollution Assessment of Beach Sediments in Balongan, Indramayu - Andi Budi Bakti; Muhammad Yudhistira Azis (Jurnal Kimia Valensi, 2026)
Balongan is a coastal area whose waters are vulnerable to contamination heavy metals due to anthropogenic activities, particularly oil refinery operations. This study aimed to (1) characterize the physicochemical properties and quantify heavy metal concentrations in sediments from Balongan; (2) identify the contamination level, sources, spatial distribution, and ecological risk; and (3) analyze inter-parameter relationships, site similarities, and dominant factors controlling contamination pattern variability using a chemometric approach. Sampling was conducted in May 2025, and heavy metal analysis was performed using F-AAS. The results showed that the concentrations of Pb, Cu, Zn, and Cr remained within safe limits, whereas Cd and Ni exceeded the threshold values. Cd was predominantly attributed to anthropogenic sources (CF>6), whereas Ni was mainly attributed to natural processes (CF<1). Although still below threshold values, Pb, Cu, Zn, and Ni concentrations were higher at sites closer to the oil refinery, suggesting influences from oil-related activities. Elevated Cd and Ni concentrations were the primary contributors to sediment toxicity, with PERI values ranging from moderate to severe. The clay fraction and organic matter showed positive correlations with heavy metals. Thus, the dominant factors controlling the variability of contamination patterns are the similarity of pollution sources and sediment physicochemical properties.